مشروع تدوير النفايات المنزلية الصلبة في مدينة بريدة - Al-Fayad, Mahmoud; Al-Muhaimed, Badr (مجلة العلوم الإدارية و الإقتصادية, 2019)
Waste disposal is a major concern for all municipalities and city secretariats around the world. With the development of eco-ecosystems, especially so-called green systems, the issue of solid waste disposal has also evolved from burning, landfill and chemical treatments to recycling and reuse. The research aims to develop an integrated plan for waste management and recycling project in Buraidah city. To achieve this objective, the researchers conducted field visits to all relevant parties, whether official or popular, in order to collect the information that enabled them to propose an organizational structure for project management and prepare an economic feasibility study so that the project is ready to monitor allocations and implementation. In addition, the study showed that the project is economically viable as evidenced by the economic feasibility study and the estimated budget for 1440H which showed that the project can generate profits of at least 22.76 million Saudi riyals. The importance of this project is shown as a road map that facilitates the implementation and execution of the project and contributes effectively to the preservation of the environment from pollution, especially air and water sources.